[Organizational and financial aspects of the introduction of Botox® in the clinical diagnostic therapeutic process of chronic migraine at a Local Health Unit in Italy] - Cioffi, Francesca; Oradei, Marco; Cerbo, Rosanna; Di Pietro, Vittorio; Riccioni, Giovanna; Pardhanani, Gianni; Capannini, Eleonora; Basile, Michele (Farmeconomia. Health Economics and Therapeutic Pathways, 2016)
BACKGROUND: Existing literature shows that the use of Botox®/onabotulinumtoxinA (BT) in chronic migraine (CM) is promising from a cost-effectiveness standpoint and the use of a clinical diagnostic therapeutic process (CDTP) dedicated to CM allows a reduction of pathology costs. The inclusion of BT in chronic migraine therapy at a Roman ASL involves the need to investigate the real treatment costs of a CDTP and to measure how a targeted organizational CDTP strategy for CM allows insuring treatment accessibility, sustainability, and appropriateness. OBJECTIVE: To conduct a cost-effectiveness analysis of providing administration of BT in patients with CM using real world data from an ASL in Rome. METHODS: The real world cost data for approximately 215 anonymous patients were summarized. The cost data were extrapolated from the database of the ASL and they populated a Markov decision model developed by Allergan. The analysis is based on a decision model populated with real drug and service cost data, for the years 2010-2012. The financial assessment was conducted from the viewpoint of the Italian National Health Service. RESULTS: Over a 2 year temporal horizon, incremental BT costs, compared to a placebo, are equal to € 261 against an incremental gain of 0.0655 QALY in favor of BT. The ratio between costs and incremental QALY generates an ICER of 3,983 €/QALY, favorable and below the acceptability threshold used by many countries for reimbursement decisions (25,000-40,000 € per QALY gained). CONCLUSIONS: The inclusion of BT in the CDTP dedicated to CM of an Italian ASL improves both clinical outcomes of the patients and the allocation of the SSN available resources. [Article in Italian]